Curved Walking Rehabilitation with a Rotating Treadmill in Patients with Parkinson’s Disease: A Proof of Concept - Godi, Marco; Giardini, Marica; Nardone, Antonio; Turcato, Anna Maria; Caligari, Marco; Pisano, Fabrizio; Schieppati, Marco (Frontiers in Neurology, 2017)
Training subjects to step-in-place eyes-open on a rotating platform while maintaining a fixed body orientation in space (podokinetic stimulation, PKS) produces a post-effect consisting in inadvertent turning around while stepping-in-place eyes-closed (podokinetic after-rotation, PKAR). Since the rationale for rehabilitation of curved walking in Parkinson's disease is not fully known, we tested the hypothesis that repeated PKS favours the production of curved walking in these patients, who are uneasy with turning, even when straight walking is little affected. Fifteen patients participated in ten training sessions distributed in three weeks. Both counter-clockwise and clockwise PKS were randomly administered in each session. PKS velocity and duration were gradually increased over sessions. The velocity and duration of the following PKARs were assessed. All patients showed PKAR, which increased progressively in peak velocity and duration. In addition, before and at the end of the treatment, all patients walked over-ground along linear and circular trajectories. Post-training, the velocity of walking bouts increased, more so for the circular than the linear trajectory. Cadence was not affected. This study has shown that Parkinsonian patients learn to produce turning while stepping when faced with appropriate training, and that this capacity translates into improved over-ground curved walking.